Fungal beta-N-acetylhexosaminidases with high beta-N-acetylgalactosaminidase activity and their use for synthesis of beta-GalNAc-containing oligosaccharides - Weignerová, Lenka; Vavrusková, Petra; Pisvejcová, Andrea; Thiem, Joachim; Kren, Vladimír (Carbohydrate research, 2003)
About 60 fungal strains were tested for production of extracellular beta-N-acetylhexosaminidases. A unique beta-N-acetylhexosaminidase with the beta-GalNAc-ase/beta-GlcNAc-ase ratio of 2.3-2.8 was found in the culture filtrates of some strains of Penicillium oxalicum. Addition of 20% (w/v) MgSO(4) increased the beta-GalNAc-ase/beta-GlcNAc-ase ratio to the value of 3.35. Cultivation conditions influence this ratio as well. beta-N-Acetylhexosaminidases from P. oxalicum CCF 2430 and Aspergillus oryzae CCF 1066 considerably differing in the GalNAc-ase activity were used for the synthesis of the following structures beta-D-GalpNAc-(1-->4)-D-GlcpNAc, beta-D-GalpNAc-(1-->6)-D-GlcpNAc, beta-D-GalpNAc-(1-->6)-D-GalpNAc, beta-D-GalpNAc-(1-->4)-alpha-D-GlcpNAcOAll and beta-D-GalpNAc-(1-->6)-beta-D-Galp-(1-->4)-alpha-D-GlcpNAcOAll to demonstrate the application of these new enzymes.
Keywords: Oligosaccharides; Molecular Structure; oligosacharidy; beta-N-acetyl-galaktosaminidasa; beta-N-acetylhexosaminidasy; beta-N-Acetyl-Galactosaminidase; molekulární struktura; beta-N-Acetylhexosaminidases; substrátová specifita; koncentrace vodíkových iontů; hexosaminidasy; Hexosaminidases; Hydrogen-Ion Concentration; Substrate Specificity; Penicillium